The Effects of Business Digitalization and Knowledge Management Practices on Business Performance: Findings from Indonesian Micro, Small, and Medium Enterprises - Sijabat, Rosdiana (UI Scholars Hub, 2022)
Studies analyzing the link between business digitalization, knowledge management practices, and business performance are rare, especially within the context of Indonesian Micro, Small, and Medium Enterprises (MSMEs). As such, this study investigates the effects of business digitalization and knowledge management practices on the performance of MSMEs. It thus offers novel insight into the mediative influence of knowledge management on the digitalization and performance of MSMEs. Primary data, collected from 95 entrepreneurs involved in MSMEs, were used to test four hypotheses regarding the effect of business digitalization on knowledge management practices and business performance using a structural equation model. This study finds that digitalization has a positive and significant effect on the knowledge management practices and business performance of MSMEs. It also finds that knowledge management practices have a positive and significant effect on business performance, as it partially mediates the influence of digitalization on business performance. This mediative influence, thus, is an important factor that should be considered when attempting to accurately describe the link between business digitalization and performance. These findings indicate that MSMEs in Indonesia should better explore the potential benefits of digitalization. Likewise, entrepreneurs and managers should attempt to better understand, adopt, and implement digital business and knowledge management practices. These practical recommendations stem from the theoretical findings of this study, i.e., that knowledge management plays an important role in the digitalization of business activities, thereby improving business performance.